Thermally Activated in Situ Doping Enables Solid-State Processing of Conducting Polymers - Kroon, Renee (Chemistry of materials : a publication of the American Chemical Society, 2019)
Free-standing bulk structures encompassing highly doped conjugated polymers are currently heavily explored for wearable electronics as thermoelectric elements, conducting fibers, and a plethora of sensory devices. One-step manufacturing of such bulk structures is challenging because the interaction of dopants with conjugated polymers results in poor solution and solid-state processability, whereas doping of thick conjugated polymer structures after processing suffers from diffusion-limited transport of the dopant. Here, we introduce the concept of thermally activated latent dopants for in situ bulk doping of conjugated polymers. Latent dopants allow for noninteractive coprocessing of dopants and polymers, while thermal activation eliminates any thickness-dependent diffusion and activation limitations. Two latent acid dopants were synthesized in the form of thermal acid generators based on aryl sulfonic acids and an o-nitrobenzyl capping moiety. First, we show that these acid dopant precursors can be coprocessed noninteractively with three different polythiophenes. Second, the polymer films were doped in situ through thermal activation of the dopants. Ultimately, we demonstrate that solid-state processing with a latent acid dopant can be readily carried out and that it is possible to dope more than 100 μm-thick polymer films through thermal activation of the latent dopant